Examining the fit of social media as a tool to share disaster-related knowledge: From the perspective of task-technology fit theory - Ishak, S. H.; Hashim, Kamarul Faizal; Ahmad, Mazida; Ahmad, M. N. (2014)
ICT is emerging as a process of knowledge-sharing without any physical and geographical constraints.ICT has successfully been used to disseminate knowledge during a constrained situation (i.e. disaster).In other words, ICT can be used to connect the public during a time of crisis.In Malaysia, the National Security Council(NSC) is one of the agencies responsible for managing disasters.Having a reputation as being a "champion of agencies", the NSC is responsible for providing a social media by which to share disaster-related knowledge with the public.Nevertheless, to what extent this social media actually supports the knowledge-sharing process is unknown.Hence, the purpose of this study is to determine the extent to which a social media actually supports the knowledge-sharing process; a theory known as Task-Technology Fit (TTF) is adopted. The data will be collected by distributing questionnaires to the users who have experience in accessing the social media tools of the NSC to acquire disaster-related knowledge during the occurrence of a disaster (i.e. flood). Structural Equation Modelling (SEM) will be used to analyze the data.The development of a theoretical research model will assist the agencies involved in disaster management to predict user evaluation of the social media tool in order to gather knowledge/information related to disasters.